DEVELOPMENT OF JOLOTUNDO TEMPLE TOURISM WITH ARCHITECTURAL SYMBOLISM APPROACH - Cahyanti, Shalsabila Putri; Vitru, Ryu; Sunarya, Wendy (ADBE, 2023)
The tourism sector contributes greatly to the development of the economy and human resources in an area. One of the tourism potentials in Indonesia that can be promoted to increase the branding of an area is a temple site which is rich in historical value. Temples also have architectural values that reflect past civilizations and cultures. Forms, styles and architectural details of temples can be studied to revive historical values of an area through new design objects that adopt temple design principles. This study focuses on examining the principles of temple design using an architectural symbolism approach in the case study of the Jotolundo Temple in the Penanggungan village area, Mojokerto, East Java. The purpose of this study is to generate conceptual architectural design ideas that are contextual with the temple site so that they can be applied to the context of the Penanggungan Village area. Literature study was conducted to identify important aspects of symbolism architecture that can be applied to the development of tourist area design ideas. Qualitative methods were also carried out in this study through field observations and interviews so that conceptual design ideas that are contextual can be generated.